Impact of Pregnancy-Related Venous Thromboembolism on Quality of Patients' Lives. (November 2021) - Al-Husban, Naser; Alnsour, Leena N.; El-adwan, Zaid; Saleh, Nada A.; El-Zibdeh, Mazen
Background: During pregnancy, the risk of venous thrombo-embolism (VTE) is increased at least five times compared with non-pregnant women of the same age, while the relative risk in the postpartum period can be as high as sixty times. The aim of the study was to explore the impact of pregnancy-related VTE on patients' mental, professional, social and personal life.Methods and Materials: Cross-sectional study at Jordan University Hospital's Obstetrics Department.Results: There were 112 women. Forty-six (41.1%) had a postpartum VTE. Twenty-eight of the patients (25%) had comorbidity. Eleven (9.9%) had a previous episode of VTE. Thirty-nine (35%) of the women reported three or more hospital visits over the past six months. Twenty-one (19.6%) of the women answered that their leg or chest pain has impeded their social activities. Anxiety/Depression was reported by 96.43% while Pain/Discomfort by 73.21%. A significant reduction of time spent on their work (correlation = 0.663, significant at <0.01) and accomplishing less work (correlation = 0.787, this was significant at <0.01) was found; 57.14% of patients indicated that VTE affecting their future pregnancies; 58.9% of patients were receiving anticoagulants with the most commonly used drug was aspirin. Twenty-four (36.4%) of the women were on multiple anticoagulant therapies. Twenty-five of the patients receiving medications do not monitor their medications and 20 patients said that monitoring the drug level was a bother to them.Conclusions: Pregnancy-related VTE had a significant adverse impact on physical, mental and professional life of women. It also had negative effects on future pregnancy plans.